Measurement of Alpha Emitters Concentration in Tomato Fruits Using CR – 39 Plastic Track Detector (Baghdad Science Journal, 2025)
Our country suffered from pollution translation as a result to the wars events, so, it is necessary to measure the amount of radiation in the fields that are of indirect contact with human life and health. The main aim of the present work is to measure the concentration of alpha emitters in tomato fruits collected from different farms in Al – Basra governorate in the south of Iraq. Nuclear track detectors of type CR – 39 are used as a detection device and Can technique as a detection technique. Results show that the maximum concentration recorded is sample no.7 of site Al – Rafidhya which was equal to (6.9621 ± 0.111) ppm and sample no.1 of site Lothan with concentration equals to (4.9236 ± 0.117) ppm. The minimum concentrations were in sample 6 of site Al – Lehaiss (1.5360 ± 0.084) ppm followed by sample 9 of site Malhan which recorded (1.6840 ± 0.111) ppm (20.208 ± 1.332 Bq/m3).